Properties of Mortar with Red Gypsum as Cement Replacement Material by Using Industrial Approach Method - Mohd Amirul Hakim, Sidek; R. M., Yunus; Fadzil, Mat Yahaya; Muhammad Faisal, Baderolhissam; Ahmad Khan, Mohamad Al-Nizar Khan (AENSI Publishing, 2017)
Utilization of Red Gypsum, a common industrial waste, in the manufacturing of cement brick can mitigate the deterioration of environment as it can preserveland piling of RG waste. X-Ray fluorescence analyzer was utilized to determine the chemical composition of Red Gypsum (RG) while sieving method was used to determine its particle size distribution. From the analyses, it can be concluded that RG properties suit the purpose of replacing cement for production of low strength mortar. A range of physical and mechanical tests were conducted on various percentage of cement replacement in RG cement bricks. This paper focused on verifying formulation and water ratio to meet the compressive strength tests needed as required for low strength mortar and the effects on the quality. From the results of this study, it can be concluded that RG cement bricks complied with the Malaysian Standard 76:1972 (Specifications for bricks and blocks of brick earth, clay or shale) for non-load bearing walls. The results also indicated that a maximum range of 60-70% replacement can be done without compromising the minimum quality of the produced bricks.